APPLICATION OF THE ACMEOLOGICAL APPROACH TO IMPROVE THE EFFICIENCY OF THE PROFESSIONAL EDUCATIONAL PROCESS (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2024)
This article discusses the development of a methodology for increasing the effectiveness of the educational process based on the acmeological approach in vocational education and the development of the process of preparing for professions by using acmetechnology, computer technology, and it also provides for obtaining a professional acme personality who owns professional abilities, orientation and competence as a result of using forms and methods of organizing vocational education and training; creating pedagogical and psychological conditions for this, establishing professionally oriented training, productive use of modern educational and information technologies based on acmeological orientation - acmeological education and training, acmeological approach, technologies aimed at personality development.